High Density and Super Ultra‐Microporous‐Activated Carbon Macrospheres with High Volumetric Capacity for CO2 Capture. (18th December 2017) - Liu, Jingjing; Liu, Xin; Sun, Yuan; Sun, Chenggong; Liu, Hao; Stevens, Lee A.; Li, Kaixi; Snape, Colin E.
Abstract: Activated carbon (AC) spheres with a diameter of 1.0–2.0 mm are synthesized from coal tar pitch for postcombustion carbon capture. The as‐prepared AC macrospheres after potassium hydroxide (KOH) activation are found to possess extraordinarily developed microporosity of which 87% is ultra‐microporosity with pore diameters less than 0.8 nm. Despite the relatively low surface area of just 714 m 2 g −1 with a pore volume of 0.285 cm 3 g −1, the macrospherical carbon adsorbents achieve exceedingly high CO2 uptake capacities of 3.15 and 1.86 mmol g −1 at 0 and 25 °C, respectively, with a CO2 partial pressure of 0.15 bar. Cyclic lifetime performance testing demonstrates that the CO2 uptake is fully reversible with fast adsorption and desorption kinetics. More importantly, due to their high bulk density of ≈1.0 g cm −3, the AC macrospheres exhibit extremely high volumetric CO2 uptakes of up to 81.8 g L −1 at 25 °C at 0.15 bar CO2, which represents the highest value ever reported for ACs. The high ultra‐microporosity coupled with the potassium‐modified physiochemical surface properties is found to be responsible for the outstanding CO2 adsorption performance of the pitch‐based AC macrospheres. Abstract : Presented are pitch‐derived activated carbon macrospheres with practical diameters of 1.0–2.0 mm, synthesized to be highly characterized with extreme ultra‐microporosities having pore diameters below 0.8 nm. The carbon macrospheres display exceedingly high gravimetric and volumetric CO2 capacities particularly at low CO2 partial pressure (15%), outperforming many reported adsorbents for CO2 capture in practical application conditions.